APLIKASI PENYEDIA JASA DRIVER MOBIL BERBASIS MOBILE DAN WEB - Rizal Shofiyul Aziz; Muhyiddin Zainul Arifin (SAINTEKBU, 2020)
Transportation is one of the needs at this time can be classified in the form of primary needs, where without a transportation it will definitely interfere with one's activities. This has an effect on the development of current technology. Even transportation-related innovations have sprung up. Departing from this, researchers found one problem that is related to the search for driver or driver services for vehicles. From this problem researchers raised an idea to build a driver or driver search system online. Researchers named this application as "Go Driver". Go Driver is an android and web platform application to search or book four-wheeled drivers, including private cars, public transport and heavy equipment transportation. In this application the user can make a booking driver by only using their respective phone. This application is built with the PHP programming language on the website section, then on the android platform using the web-view method that is configured using android studio.